BAURAN PEMASARAN DAN LOYALITAS KONSUMEN HANDPHONE BLACKBERRY - Amron Amron (AMIK Jakarta Teknologi Cipta Semarang, 2015)
This study used asample ofBlackBerry mobile phoneusersinKudus with 103respondentsThis sample usingcriteria:the respondentswhohave usedandhave aBlackBerry mobile phonealeast1year.Samplingtechniqueusingpurposive samplingisa sampling techniquebased onacertaintype ofpersonwhocanprovidethe appropriate informationthathas beenset bytheresearchers. Data collection techniques inthis study usingan ordinalscalewhilemakingtechniquereferstothe Likertscale. This research has found that the biggest variableaffectedtheconsumerloyaltyis aqualityproduct, it indicatesthatthe BlackBerrycontinuestomaintainandimprove thequality of its products, among others, by improvingfeaturespackaging(casing), colorvariationandthe like.Smallestvariablesthat affectconsumerloyaltyistheprice, expectedBlackBerrymight consider includingthe pricevariablesin makingpoliciesrelated toenhancingcustomer loyalty. For example by applyingthe priceaccording tothetargetsegmentandcompetitioncurrentlyworked byBlackBerry.Keywords: product, price, distribution, consumerloyalty.